Preferred Strategies for Delivering Health Information to Patients With Musculoskeletal Disorders: A Qualitative Study. Issue 1 (January 2022) - Lopez-Olivo, Maria A.; des Bordes, Jude K. A.; Jibaja-Weiss, Maria; Volk, Robert J.; Suarez-Almazor, Maria E.
Abstract : Background: Patients' information needs may differ from what their care providers may perceive to be the patients' needs. This discordance needs to be recognized and addressed. Objective: We conducted a qualitative study to explore the perceptions of patients with selected musculoskeletal disorders and those of rheumatologists, on their preferred strategies for delivery of disease management information. Methods: Fifty-two patients diagnosed with either rheumatoid arthritis, knee osteoarthritis, or osteoporosis took part in 6 focus groups and 18 individual semistructured interviews. In addition, 11 rheumatologists participated in 2 focus groups and 4 semistructured individual interviews. Data were explored by thematic content analysis. Perceived preferences were identified and compared between patients and rheumatologists regarding ( a ) media, ( b ) setting, ( c ) messengers, and ( d ) key message content. Results: Patients' preferred media for disease management information were electronic (television and videos delivered as digital optical discs or the Internet), group instruction, and printed material. Patients preferred the information to be delivered in the setting of their homes, doctor's offices, or clinic waiting areas by the rheumatologists and patients with disease experience, addressing healthy lifestyle changes, medication adherence, and consequences of noncompliance. For rheumatologists, the perceived preference for information delivery was through printed material (brochures, booklets, and pamphlets) delivered in waiting areas by nurses and physicians, addressing nature of the disease, complications, and treatment adverse effects. Conclusions: Provider perspectives on strategies for education may differ from those of patients. Our findings highlight the need for considering different stakeholder perspectives in designing educational tools and decision support materials for patients with chronic diseases. Take-Home Message: Rheumatologists' preferences on strategies for education (mode of delivery, delivery setting, messengers, and topics) differ from those of patients. For example, patients want to learn about lifestyle changes and consequences of compliance versus noncompliance, whereas rheumatologists considered more important for patients to understand their disease, treatment adverse effects, and consequences of noncompliance. Abstract : Supplemental digital content is available in the text.